Expression of the melanoma cell adhesion molecule in human mesenchymal stromal cells regulates proliferation, differentiation, and maintenance of hematopoietic stem and progenitor cells - Stopp, Sabine (Ferrata Storti Foundation, 2013)
The melanoma cell adhesion molecule defines mesenchymal stromal cells in the human bone marrow that regenerate bone and establish a hematopoietic microenvironment in vivo. The role of the melanoma cell adhesion molecule in primary human mesenchymal stromal cells and the maintenance of hematopoietic stem and progenitor cells during ex vivo culture has not yet been demonstrated. We applied RNA interference or ectopic overexpression of the melanoma cell adhesion molecule in human mesenchymal stromal cells to evaluate the effect of the melanoma cell adhesion molecule on their proliferation and differentiation as well as its influence on co-cultivated hematopoietic stem and progenitor cells. Knockdown and overexpression of the melanoma cell adhesion molecule affected several characteristics of human mesenchymal stromal cells related to osteogenic differentiation, proliferation, and migration. Furthermore, knockdown of the melanoma cell adhesion molecule in human mesenchymal stromal cells stimulated the proliferation of hematopoietic stem and progenitor cells, and strongly reduced the formation of long-term culture-initiating cells. In contrast, melanoma cell adhesion molecule-overexpressing human mesenchymal stromal cells provided a supportive microenvironment for hematopoietic stem and progenitor cells. Expression of the melanoma cell adhesion molecule increased the adhesion of hematopoietic stem and progenitor cells to human mesenchymal stromal cells and their migration beneath the monolayer of human mesenchymal stromal cells. Our results demonstrate that the expression of the melanoma cell adhesion molecule in human mesenchymal stromal cells determines their fate and regulates the maintenance of hematopoietic stem and progenitor cells through direct cell-cell contact.